Empowerment Evaluation Blog - Fetterman, David (2006)
This blog, by Dr David Fetterman, provides a range of resources on emp owerment evaluation theory and practice. The blog includes links to vi deos, guides and relevant academic literature that provide a detailed analysis and discussion of using empowerment evaluation.